Comparison of changes in the muscle strength potential of elbow flexors and extensors in adolescents following a six-week programmed exercise with modified repetitive muscle loads - Vuksanovikj, Vladimir (Faculty for Physical Culture, University of St. Cyril and Methodius, Skopje, Republic of Macedonia, 2012)
The research analyses and compares the changes of the maximum strength potential, isokinetic parameters and measures for anthropometric indicators realised in accordance with standard methods and echo sonography, between flexor muscles and extensor muscles, as well as the genetic predisposition for strength capacity development of the subjects. The experimental procedure included 21 subjects, divided into 3 experimental groups, pilot research homogenised. Individually focused programme for maximum strength capacity was realised, through exercises on Scott bench for the elbow flexor and extensor muscles during a 6-week period. The first group worked in a classic method, loading the muscle tissue along the entire elbow amplitude. The second group worked in an elbow reduced contractions methods in conditions when the muscle tissue exhibits maximum load. The third group also worked in a reduced contractions method, but in conditions when the muscle tissue can endure maximal external load. Statistical analysis showed positive effects of the experimental programme for transformation of the maximal strength capacity for both muscle parties in the three experimental groups. Data obtained from the three control points speak of similar tendency of the three experimental groups, although the subjects carried out different tasks. The elbow flexor and extensor muscle groups endured similar strength capacities transformation. The hypothesis on the association of strength capacities with the ACTN3 genotype was not confirmed from the muscle tissue genetic dominance analysis.
Споредба на промените на силовиот мускулен потенцијал на флексорите и екстензорите на зглобот на лакотот кај адолесценти по шест неделно програмирано вежбање со модифицирани репетитивни напрегања
Keywords: exercise, flexor muscles, extensor muscles, maximal muscle strength, biodex, isokenitcs, reduced amplitude, elbow, anthropometry, echo sonography, ACTN3 genetic analysis, experimental groups, longitudinally.